The management of primary nonparasitic splenic cysts - Boybeyi, Ozlem; Karnak, Ibrahim; Tanyel, F Cahit; Ciftçi, Arbay O; Senocak, M Emin (The Turkish Journal of Pediatrics, 2010)
Primary nonparasitic splenic cysts (PNSC) are rare and their management in children has been controversial. We conducted this study to discuss various treatment modalities. The medical records of patients with PNSC (1991-2008) were evaluated retrospectively, including age, sex, history of trauma, presenting symptoms, physical examination and radiological findings, therapeutic approaches, and outcomes. Six patients, between 3 to 12 years of age with a male/female ratio of 2, were included. The presenting symptom was abdominal pain in all but one asymptomatic patient. Physical examination findings were unremarkable in all except for palpable spleen in two patients. Cyst sizes ranged from 3 x 4 cm to 10 x 12 cm. The patients were treated with aspiration-sclerotherapy (n=2), total splenectomy (n=2), partial splenectomy (n=1), and cyst excision (n=1). The pathological diagnoses were epidermoid cyst (n=5) and lymphangioma (n=1). The postoperative course was uneventful except for postsplenectomy fever (n=1), recurrence (n=1) and residual cyst (n=1). PNSC larger than 5 cm in diameter or those that are symptomatic should be treated surgically. Total splenectomy should not be done in children to avoid infectious postsplenectomy problems unless there is a mandatory condition like intraoperative bleeding. Aspiration-sclerosis is not recommended because of recurrence.